2010
DOI: 10.2109/jcersj2.118.217
|View full text |Cite
|
Sign up to set email alerts
|

Ion implantation and diffusion behavior of silver in zinc oxide

Abstract: Silver implantation (75 keV, 2 × 10 14 ions/cm 2 ) in ZnO ceramics was carried out at room temperature to characterize the diffusion phenomenon. Annealing caused Ag evaporation from the sample. Results suggest that it is difficult to incorporate Ag into Zn site by annealing. The Ag profile with the monotonous decrease in concentration below 3 × 10 17 /cm 3 was observed in ZnO annealed at 900°C. Above results become the basic results for producing the ZnO sensor used the reaction at surface and the grain bounda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 14 publications
(9 reference statements)
0
5
0
Order By: Relevance
“…This stems from the different valence states of Ag and Zn as well as from the larger Ag ionic radius when compared to that of Zn . Sakaguchi et al investigated the diffusion of Ag in polycrystalline ZnO in the temperature range 700–900 °C . They found a Ag diffusion coefficient in ZnO equal to 7.8 × 10 –13 cm 2 /s at 900 °C.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This stems from the different valence states of Ag and Zn as well as from the larger Ag ionic radius when compared to that of Zn . Sakaguchi et al investigated the diffusion of Ag in polycrystalline ZnO in the temperature range 700–900 °C . They found a Ag diffusion coefficient in ZnO equal to 7.8 × 10 –13 cm 2 /s at 900 °C.…”
Section: Resultsmentioning
confidence: 99%
“…60 Sakaguchi et al investigated the diffusion of Ag in polycrystalline ZnO in the temperature range 700−900 °C. 61 They found a Ag diffusion coefficient in ZnO equal to 7.8 × 10 −13 cm 2 /s at 900 °C. For a lower temperature range, McBrayer et al 62 studied metal diffusion in SiO 2 oxide layers and reported that the Ag diffusion coefficient, D, is equal to 10 −15 cm 2 /s at a temperature of 221 °C, which is typically the measured temperature associated with the AgNW network failure.…”
Section: Acs Applied Materials and Interfacesmentioning
confidence: 98%
“…Furthermore, since Ag is a group 11 (I-b) element, Ag doping has been reported as a possible way to form acceptor states in ZnO, if the Ag ion occupies a substitutional Zn site (Ag Zn ), therefore achieving p-type conductivity 21 -24 . However, Ag is considered to have a low solubility in ZnO at equilibrium conditions, since the Ag ion has a different valence state than ZnO and a larger ionic radius, so diffusion of the Ag to the surface of the ZnO is frequently observed 25 . The production of this type of ZnO/metal composites usually involves procedures as calcination, sputter or electrophoretic deposition of metals in the ZnO surfaces 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Zinc oxide (ZnO)‐based ceramics are used in various applications including varistors, gas sensors, thermoelectric devices, and piezoelectric transducers, to mention a few. Hence, significant efforts have been made in the past to develop processes that would increase the density (i.e., greater than 95%) of ZnO‐based ceramics .…”
Section: Introductionmentioning
confidence: 99%